(untitled) (Nóema, 2017)
This paper aims to show briefly how the consideration of the influence of Spinoza over Sini’s thought represents an excellent starting point in order to understand his concept of philosophical practice. Starting from Sini’s interpretation of Spinoza’s Ethics, as it is developed in Archivio Spinoza. La verità e la vita, I bring up the subjects of philosophical exercise, «limit» and «logic of finite», the relashionship between subject and object and, above all, the ethical core of philosophy.